Una sfida possibile: la teoria della nascita in altri ambiti linguistici - Todestrieb und Erkenntnis Lipsia, 19 marzo 2011 - Fagioli, Massimo (Il sogno della farfalla, 2023)
In 2011 the German translation of the volume Death instinct and knowledge was published by the Stroemfeld publishing house. During the book presentation, which took place at the Book Fair in Lipsia, the author Massimo Fagioli, with a specific reference to Kafka’s work, proposes a reflection about his connection with both the German language and culture.